Is there a primordial Torah? - Lebens, Samuel (International journal for philosophy of religion, 2017)
Is Orthodox Judaism committed to the existence of a Torah that pre-existed the world? This paper argues that Orthodoxy is so committed unless it can find compelling philosophical or theological reasons to reject the possibility of such an entity, and then to re-interpret allegorically all of the texts that speak of such a Torah. Providing an ontology of primordial texts, I argue that no compelling reason can be found to deny the existence of the primordial Torah.